The Effectiveness of Science Textbook Based on Science Technology Society for Elementary School Level - Alifah Kartikasari; Roemintoyo Roemintoyo; Sri Yamtinah (Institute of Advanced Engineering and Science, 2018)
This study reports a quasi-experimental investigating the development of Science textbook based on Science Technology and Society for elementary school. The data collection was got from the achievement test (pretest-posttest). The population was all fourth-grade students of elementary schools in Gatak Subdistrict and the sample of the study was two schools as an experimental class and control class. The research sample was taken by random sampling technique. The results of this research showed that there was an improvement of student achievement before and after the implementation of science textbook based on Science Technology and Society. The result of the independent sample t-test shows that tobs is higher than table (5.489>1.681). The outcomes of the learning improvement in the experimental class based on the acquisition of N-Gain scores of 0.558. Based on tobs results, H0 is rejected. So it can be concluded that the development of a science textbook based on Science Technology Society in elementary school is appropriate to use for learning.